The effect of PjBL-integrated STEM on students' cognitive learning abilities class x high school - Aurelya, Vinna Asya; Carolina , Hifni Septina (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2024)
PjBL-integrated STEM learning appears to impact increasing student motivation, interest, and engagement positively, thus potentially improving students' cognitive learning outcomes. The purpose of this research is to determine the effect of the PjBL-integrated STEM learning model on the cognitive learning abilities of grade x high school students. This research is quasi-experimental with a nonequivalent control group design. The research sample was 36 students involved in the experimental class and control class with class x status at SMAN 5 Metro City. The research instrument was 25 multiple-choice questions given to students in the pretest and posttest. The research data are in the form of pretest and posttest scores. The difference in pretest and posttest scores is indicated by the n-gain value. The data analysis technique is through the t-test. The results of the study showed that there was no significant effect of PjBL-integrated STEM learning on students' cognitive abilities because the N-gain value of the experimental class was smaller than the N-gain value of the control class (55.42 < 56.26). However, there was a difference between the two classes (t hit 1.66 > t tab -5405). The research results concluded that PjBL-integrated STEM learning had no effect on increasing students' cognitive abilities. Teachers need to understand PjBL-integrated STEM learning to create active and effective learning classes.